Eco-development in China Cities, Communities and Buildings - Deng, Wu (Palgrave Series in Asia and Pacific Studies, 2018)
This book explores China's eco-development strategies and practices from a multi-scalar perspective, discussing the importance of interplay between multi spatial levels of the built environment, as well as the stakeholders who are key players for China's eco-development. Based on a selection of eco-development Chinese case studies - eco-city, eco-community and eco-building - it highlights how specific eco initiatives and green features are applied and practiced, offering a guide to China's strategy directions and design and planning trends. The book identifies gaps and strategies and solutions for future eco-development expected to take place in China in the coming decades, as well as useful references for eco-development in other countries, and provides a useful resource for studies in the fields of urbanism, sustainable development and eco-design.